IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM PENCEGAHAN PERUNDUNGAN (BULLYING) DI SMP YPU KOTA BANDUNG - Sulaeman, Pian Supriatna; Kurniawan, Saepul; Azhari, Asan; Rosmaladewi, Okke; Iriantara, Yosal (LPPM UNINUS, 2024)
Bullying is a serious problem in the world, which can damage the physical and mental health of the parties involved. The problem of bullying cannot be ignored, especially in the school environment where at this age someone is experiencing growth which is very important for their future. Prevention of bullying can also be done through activities within the school, one of which is the Pancasila Student Strengthening Project program. This community service (PKM) aims to describe the activities of students at SMP YPU Kota Bandung, related to the Strengthening Pancasila Student Profile Project. This activity is one of the activities at school to support the implementation of the new curriculum, namely the Independent Learning Curriculum. The research method used is a qualitative method through direct observation of subjects and objects at SMP YPU Kota Bandung. Apart from that, it is also supported by documentation related to the activities carried out at the school. The results of this research were that SMP YPU Kota Bandung took the theme